Confidentiality in Arbitration and the Limits of Legal Transparency: Reassessing the Balance Between Private Autonomy and Public Accountability - Fitria Mukhtar Siregar; M. Abdillah; Suci Hidayati Malau; Raja Muda Pahlevi Siregar; Azka Rayyani (Jurnal Cendikia ISNU SU, 2026)
The increasing reliance on arbitration as a mechanism for resolving commercial disputes has reinforced the importance of confidentiality as one of its defining characteristics. While confidentiality protects commercial interests, trade secrets, and sensitive business information, its extensive application has generated growing concerns regarding legal transparency, judicial accountability, and public access to legal reasoning. This study examines the legal relationship between confidentiality and transparency in arbitration and evaluates the extent to which these competing principles can be reconciled within the Indonesian arbitration framework. Employing normative legal research with statutory, conceptual, and comparative approaches, the study analyzes Law Number 30 of 1999 on Arbitration and Alternative Dispute Resolution alongside international arbitration instruments, institutional rules, and relevant legal scholarship. The findings demonstrate that confidentiality should not be regarded as an absolute principle but rather as a proportional legal mechanism whose application must be balanced against broader interests of legal certainty, public accountability, and the development of arbitration jurisprudence. Although confidentiality remains essential for protecting commercial privacy and preserving business confidence, excessive secrecy may hinder legal development, restrict access to legal information, and weaken the legitimacy of arbitral dispute resolution. Accordingly, limited judicial supervision, controlled disclosure through anonymized arbitral awards, and strengthened digital information security provide an appropriate balance between commercial confidentiality and legal transparency. This study contributes to arbitration scholarship by proposing a proportional interpretation of confidentiality that preserves commercial autonomy while accommodating transparency where required by public interest, judicial accountability, and the coherent development of arbitration law.